ATM transaction simulation: combination of ACDs and cox process - Habibi, Reza (Journal of numerical analysis and approximation theory, 2025)
Two main approaches for analyzing the ultra-frequency data such as ATM (auto teller machine) transaction are Cox process and autoregressive conditional durations (ACDs). This paper combines both models and proposes some simulated results. The functional data analysis proposes useful method for modeling the intensity of Cox process. A real data set is also proposed. Conclusions are also given.